BMC Nursing - SpringerLink (Online service) (London : BioMed Central : Imprint: BioMed Central.)
BMC Nursing is an open access, peer-reviewed journal that considers articles on all aspects of nursing research, training, education and practice.
Keywords: Medicine; Nursing; Nursing administration; Medicine & Public Health; Nursing; Nursing Management; Nursing Research